Recipes for Change validation report: Sweet Sour Cat Fish Soup in Vietnam - Norman, James (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
The main climate risks to catfish production in the Mekong Delta are: (i) sea level rise and its detrimental consequences, such as saltwater intrusion and heightened flood risk; (ii) changes in rainfall patterns and consequent river flow, which are expected to result in an increase in flooding and drought, as well as the potential for decreased freshwater availability in some areas; (iii) rising temperatures which may alter breeding and growing rates among fish, and increase organic decomposition and eutrophication, leading to higher costs for aeration machinery. The key adaptation measures for managing the foreseen impacts of climate change within the region comprise: (i) infrastructural measures, including dyke heightening/reinforcement, improved water storage and water management; (ii) practice and technology, including the relocation of production, modified stocking cycles/rates and development of salt-tolerant species.